Opportunities For Innovative Development of Transport Services in The Republic - Mirzaev Kulmamat Djanzakovich (Academia One, 2024)
The study of scientific and practical aspects of the regulatory framework of the transport industry of the republic is considered one of the important tasks.
Keywords: Innovation; innovative transport services; transport infrastructure